GAMIFICATION-DRIVEN E-LEARNING MANAGEMENT FOR IMPROVED SELF-REGULATED LEARNING: MEDIATING EFFECTS OF MOTIVATION AND ENGAGEMENT WITH LEARNING ANALYTICS SUPPORT - Lia Saniah; Siti Saodah Susanti (Program Studi PGSD Universitas Flores, 2026)
Independent learning process management is commonly expected of students in online learning contexts; however, many students struggle to maintain motivation and engagement, which may hinder the development of Self-Regulated Learning (SRL). Students' motivation, engagement, and self-regulation in digital learning contexts need to be supported by instructional approaches, as this condition emphasizes. This study aims to explore the impact of integrating Learning Analytics Support into gamification to enhance student motivation and engagement, thereby strengthening Self-Regulated Learning (SRL) in online learning. This quantitative study uses Structural Equation Modeling (SEM) to analyze data collected from 100 students in senior high schools in Cianjur Regency. The results show that gamification greatly enhances SRL by raising student involvement and motivation. Motivation and engagement act as key mediators in the relationship between gamification and SRL, with gamification enhancing these factors through elements such as points, badges, and leaderboards, which encourage active participation and sustained effort. While Learning Analytics Support (LAS) did not show a significant direct effect on SRL, its role in providing real-time feedback and tracking progress supports the development of self-regulation when combined with gamification. These findings suggest that integrating gamification with learning analytics can create a learning environment that supports students’ motivation, engagement, and self-regulated learning in online education. This study offers insights into the potential of combining these approaches to improve the effectiveness of digital learning strategies and enhance students' ability to manage their own learning processes.